47.1k views
4 votes
3y - 4 = 6 - 2y
help

2 Answers

4 votes

Answer:

y = 2

Explanation:

First you need to get rid of one of the variables so you need to move it to the other side of the equation. When you do so, the sign changes and becomes either positive or negative so

if we move y it will be like this

(3y - 3y) -4 = 6 - 2y - 3y 3y became negative

-4 = 6 -5y

then we do the same thing to 6 so

-6 -4 = -5y

-10 = -5y

then we divide -10/-5 = 2

so, y = 2

User Paul Ardeleanu
by
4.9k points
3 votes

Answer:

y = 2

Explanation:

3y - 4 = 6 - 2y

→ Add 2y to both sides to isolate 6

5y - 4 = 6

→ Add 4 to both sides to isolate 5y

5y = 10

→ Divide both sides by 5 to find the value of y

y = 2

User Awrigley
by
5.2k points